Communication Convergence in Contemporary China International Perspectives on Politics, Platforms, and Participation - Dodge, Patrick Shaou-Whea (Book collections on Project MUSE., 2020)
"As the United States and China increasingly come together, and while convergence is bringing together communication technologies, people, and platforms in new ways, it also raises key questions in terms of information flows, control, and regulation-and hence the future of US-Chinese relations. The case studies that comprise this book document the ongoing changes, challenges, and transformations within these processes, offering readers informative snapshots of how US-Chinese relations are changing on the ground, in the lived realities of daily communication habits"--